2010
DOI: 10.1007/s11269-010-9634-8
|View full text |Cite
|
Sign up to set email alerts
|

The Integrated Management of Water Resources in Marina Baja (Alicante, Spain). A Simultaneous Equation Model

Abstract: In the Marina Baja region there is a tradition of fierce competition for water resources which necessitates the regulation of institutions in order to satisfy the interests of the different water users. The management of the water resources in this region is based on the water exchange between the different users with no legal modification of the water concessions. This situation requires continuous negotiation in order to maintain the balance between urban, tourism and the agricultural demand. In this article… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 62 publications
(66 reference statements)
0
9
0
1
Order By: Relevance
“…However, Agthe et al [1986] suggest that constructing simultaneous equations for short‐ and long‐run elasticities can help to correct the bias. This method has been supported in more recent research [ Espey et al , 1997; Torregrosa et al , 2010]. Torregrosa et al [2010] found that constructing a simultaneous equation model corrected for multicollinearity and serial autocorrelation while allowing the endogenous dependent variables to be simultaneously and jointly determined by a set of exogenous factors.…”
Section: Methodological Reviewmentioning
confidence: 97%
See 1 more Smart Citation
“…However, Agthe et al [1986] suggest that constructing simultaneous equations for short‐ and long‐run elasticities can help to correct the bias. This method has been supported in more recent research [ Espey et al , 1997; Torregrosa et al , 2010]. Torregrosa et al [2010] found that constructing a simultaneous equation model corrected for multicollinearity and serial autocorrelation while allowing the endogenous dependent variables to be simultaneously and jointly determined by a set of exogenous factors.…”
Section: Methodological Reviewmentioning
confidence: 97%
“…This method has been supported in more recent research [ Espey et al , 1997; Torregrosa et al , 2010]. Torregrosa et al [2010] found that constructing a simultaneous equation model corrected for multicollinearity and serial autocorrelation while allowing the endogenous dependent variables to be simultaneously and jointly determined by a set of exogenous factors. This approach produced an adjusted R 2 value above 0.95.…”
Section: Methodological Reviewmentioning
confidence: 97%
“…In fact, Spain is the European Union country with a greater number of second homes (Olcina, Saurí and Vera 2016), considered as such when they are not the usual place of residence and are used at least fifteen days per year (Torregrosa et al 2010). Real estate development in Spain cannot be understood without considering the strong investments made by foreigners .…”
Section: Study Areamentioning
confidence: 99%
“…Although the territorial scale used does not allow to verify the variance of the variables within the municipalities, several methodological questions have required this choice, as has happened in other cases of study in Spain (March and Saurí 2010;Torregrosa et al 2010).…”
Section: ; Kontokosta and Jain 2015)mentioning
confidence: 99%
“…The coexistence of the so-called humid Spain (north and northeast of the country) with the south and south-east, known as dry Spain, together with a significant development of the tourist sector, a large water user, in the driest area of the country, has given rise to the emergence of water management practices with local characteristics [107]. In this context, water problems have two dimensions: the physical dilemma of irregular distribution in terms of time and territory, and the politico-institutional complexity of a management of water resources which has been focused for a long time on supply-side approaches associated with a series of negative environmental impacts, in particular, reservoirs, basin transfers and desalination [108].…”
Section: Spain: When Water Exchange Guarantees Water Supplymentioning
confidence: 99%